A desigualdade racial no Brasil nas três últimas décadas - Rafael Guerreiro Osorio (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This paper presents a brief review of the main sociological theories on socioeconomic inequality between blacks and whites in Brazil, and indicators of racial income inequality for the period 1986-2019, based on the National Household Survey (PNAD). The indicators show that, despite all the change in racial relations in the period, such as the debunking of the myth of racial democracy, the growing appreciation of blackness and the greater denunciation and repudiation of racism and discrimination, in the income dimension there was only a tiny reduction of inequality. Racial income inequality persists without substantive upheavals. The average income of whites is at least twice that of blacks, and this difference, according to the decomposition of the Theil L indicator, accounts for 11% of the Brazilian income inequality. The contribution of income inequality among blacks to total inequality in Brazil increased, together with the share of the population that declares being preto and pardo in the PNAD, which became the majority in the period.
Keywords: I30; J15; J62; J71; 330; racial inequality; income inequality; PNAD; PNAD Contínua